Clinical perspectives on the influence of drug formulation on patient tolerability and use of commonly prescribed antidepressants in major depressive disorder - Matthew A Fuller; Martha Sajatovic; Lata Handiwala (Archives of Global Professionals, 2013)
The purpose of this review is to summarize the formulation options for currently available antidepressants, and discuss examples of the influence that formulation may have on the pharmacologic and clinical profiles of the medications. A review of current literature suggests that differences in drug-delivery technologies can lead to variations in the pharmacokinetic and pharmacodynamic profiles of generic and branded drugs, despite generic drugs being required to meet bioequivalence standards compared with their branded counterparts. These differences may influence the effectiveness and tolerability of treatment. Recent reports have highlighted the need for individualized treatment regimens and careful assessment of tolerability and efficacy when switching patients from brand to generic formulations. There is a growing body of evidence indicating that differences in formulation can substantially impact drug pharmacokinetics and pharmacodynamics, which in turn, can affect drug effects. The clinical impact of these differences remains unclear. Further research is needed to clarify the influence of antidepressant formulations on treatment adherence, patient preference, and quality of life, and how this impacts clinical practice with regard to brand versus generic treatment selection.